Tahap Penetuan Calon Kepala Daerah Kota Medan Tahun 2010 di Partai Demokrat - HENDRA KURNIAWAN MANIK (Politeia: Jurnal Ilmu Politik, 2012)
Democratic Party is one of the political parties that participation in the General Election of Regional Head (Pemilukada) in Medan City. There are some names that are register oneself to be the candidates mayor and deputy mayor of Medan City compete in this party. They are Deny Ilham Panggabean, Nurhasanah, Rahudman Harahap, Dzulmi Eldin, Safwan Hayat, Tenang Malem Tarigan, Bahdin Nur Tanjung, Maulana Pohan, Koln (inf.) Ahwan Asmadi, Amin Daulay. This study explores the recruitment procces of the candidate conducted by the Demo-cratic Party in 2010. Collecting data of this study is using field research. The finding is there are three main stages to determine the candidate from Democratic party. The first stage is establishment of Team 9; The second stage is the registration and verification; The third stage is setting and proposing the Candidate Regional Head to the Central Board (Dewan Pimpinan Pusat). The result show that Rahudman Harahap/Dzulmi Eldin is the candidate for mayor/deputy mayor of Medan City from Democratic Party in Pemilukada Kota Medan 2010.Keywords: Local election, political party, political recruitmen.